Motion Equation Modeling of LCC-HVDC Stations for Analyzing DC and AC Network Interactions - Lu, Jun; Yuan, Xiaoming; Hu, Jiabing; Zhang, Meiqing; Yuan, Hao (IEEE transactions on power delivery, 2020)
Line-commutated converter based high voltage direct current (LCC-HVDC) transmissions are widely applied in delivering large-capacity electricity in China. Multiple large-capacity LCC-HVDC transmissions strengthen dynamic coupling between AC and DC networks. Existing literature has reported some stability problems caused by dynamic interactions between AC and DC power grids, however, the mechanism behind these problems has not been totally understood and revealed. To analyze dynamic interactions between AC and DC power grids, this article presents a small-signal model to understand the external characteristics of LCC-HVDC stations based on the motion equation concept. Comparison of time-domain simulation response with the detailed switching model shows that the proposed model can hold main behaviors of concern. Dynamic interactions between AC and DC power grids are studied based on the proposed model in multi-infeed LCC-HVDC systems. Analytical results demonstrate that there exists power dynamics in receiving AC grid when sending AC grid subjects to a disturbance, and effects of converter stations' controller parameters on power dynamics are explained by the physical relationship among state variables of the proposed model.